The Interplay of Standardized Tests and Incentives – An Econometric Analysis with Data from PISA 2000 and PISA 2009 - Christoph Helbach (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Since their first implementation in 2000, the PISA studies have attracted public attention and spurred the demand for institutional changes in schooling systems. The introduction of standardized student tests and of incentives for schools and teachers are notable examples of such institutional changes. This paper examines the effects of these particular developments. Identification is based on within-country variation between PISA 2000 and PISA 2009. The results indicate that comparing schools by means of standardized student test results is a promising measure, while evaluating teachers this way decreases the overall performance of a schooling system. The discussion provides possible explanations for these ambiguous findings. – – Die PISA-Studien haben die Bildungspolitik in den vergangenen Jahren zunehmend in den Fokus der Öffentlichkeit gerückt und die Diskussion um Reformen von Schulsystemen neu entfacht. Standardisierte Tests für Schüler und Anreizsysteme für Schulen und Lehrer sind prominente Beispiele für solche Reformen. Die vorliegende Studie untersucht die Auswirkungen dieser Entwicklungen mit Hilfe eines Panels aus den Daten von PISA 2000 und PISA 2009. Die Ergebnisse deuten darauf hin, dass die Kopplung von Anreizen für Schulen mit standardisierten Tests die Leistungen der Schüler verbessert. Im Gegensatz dazu führen Lehreranreize zu signifikant schlechteren Resultaten, wenn sie auf standardisierten Tests basieren. Mögliche Erklärungen für diese Resultate werden diskutiert.
Keywords: I20; I21; I29; 330; Education economics; incentives; standardized tests; PISA